2012
DOI: 10.1136/thoraxjnl-2012-202103
|View full text |Cite
|
Sign up to set email alerts
|

The DECAF Score: predicting hospital mortality in exacerbations of chronic obstructive pulmonary disease

Abstract: Background Despite exacerbations of chronic obstructive pulmonary disease (COPD) being both common and often fatal, accurate prognostication of patients hospitalised with an exacerbation is difficult. For exacerbations complicated by pneumonia, the CURB-65 prognostic tool is frequently used but its use in this population is suboptimal. Methods Consecutive patients hospitalised with an exacerbation of COPD were recruited. Admission clinical data and inhospital death rates were recorded. Independent predictors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
339
5
20

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(388 citation statements)
references
References 32 publications
24
339
5
20
Order By: Relevance
“…4 Patients experience on average 1-3 treated exacerbations per year 5 with up to 10% of patients dying during a hospital admission for AECOPD 6 and up to 25% within a year of admission for AECOPD. 7 Pulmonary rehabilitation is a key component of the multi-disciplinary management of COPD 8 and can improve exercise capacity, dyspnoea, activities of daily living, muscle strength, self-efficacy, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…4 Patients experience on average 1-3 treated exacerbations per year 5 with up to 10% of patients dying during a hospital admission for AECOPD 6 and up to 25% within a year of admission for AECOPD. 7 Pulmonary rehabilitation is a key component of the multi-disciplinary management of COPD 8 and can improve exercise capacity, dyspnoea, activities of daily living, muscle strength, self-efficacy, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in order to define a specific score evaluating the prognosis of hospitalized AECOPD, an English prospective study [24] involving more than 900 patients has found the five strongest independent predictors of death during hospitalization (extended MRC Dyspnoea Score, eosinopenia, consolidation, acidaemia, and atrial fibrillation), then combined into a clinical prediction score (DECAF, Dyspnoea, Eosinopenia, Consolidation, Acidaemia and atrial Fibrillation). Supported by an internal bootstrap validation, the DECAF score [24] demonstrates excellent ability in the discrimination of patient deaths during hospitalization (area under the receiver operator characteristic curve-AUC = 0.86, 95% CI 0.82 to 0.89).…”
Section: Introductionmentioning
confidence: 99%
“…However, DECAF showed consistent and excellent discrimination in the derivation and validation studies (area under the receiver operator characteristic (AUROC) curve 0.86 and 0.83 respectively) [3,4] and outperformed BAP-65, which performed inconsistently (AUROC 0.65 and 0.77 respectively). One potential weakness of BAP-65 is that the assessment of mental status may vary, despite their claim that the BAP-65 indices are objective.…”
mentioning
confidence: 99%
“…Furthermore, the provision of salbutamol nebulisers by paramedics prior to admission can elevate pulse rate, and reduce its prognostic power. In the DECAF derivation study [3], pulse rate was not associated with in-hospital mortality.…”
mentioning
confidence: 99%